ChemInform Abstract: Oxidative Cycloaddition of Aldoximes with Maleimides Using Catalytic Hydroxy(aryl)iodonium Species. Issue 50 (November 2016) - Yoshimura, Akira; Nguyen, Khiem C.; Rohde, Gregory T.; Saito, Akio; Yusubov, Mekhman S.; Zhdankin, Viktor V.
Abstract: The method is suitable for the preparation of various N‐unsubstituted pyrrolo‐isoxazoles and N‐methylated analogue (VIc), where both aromatic and aliphatic aldoximes can be used as substrates.